QARAQALPAQ TILINDE INGLIS TILINDEGI IT-TERMINLERDIŃ BEYIMLESIWI: MORFOLOGIYALÍQ HÁM FONETIKALÍQ ÓZGEShELIKLERI - Keunimjaeva, M.O. (ILIM hám JÁMIYET, 2025)
The article explores the adaptation of information technology (IT) terms and word formation processes in the Karakalpak language under the global dominance of the English language. Based on a contrast analysis, the features of word-formation models in the Karakalpak and English languages, the main mechanisms of borrowing (transcription, transliteration) are determined. Studies show that despite their deep typological features (agglutinative and analytical structure), both languages demonstrate high potential in creating new vocabulary by adapting universal nominative strategies such as composition and affixation to their linguistic systems.